Knowledge Sharing, Knowledge Use, Knowledge Storage For Banking Employee Performance Improvement: Berbagi Pengetahuan, Penggunaan Pengetahuan, Penyimpanan Pengetahuan Untuk Peningkatan Kinerja Karyawan Perbankan - Sumartik; hariasih, Misti; Sukma Nirwana, Nihlatul Qudus; Mariani, Anti; Mahendra, Danar Putra (Procedia of Social Sciences and Humanities, 2022)
The company's competitive advantage can be seen from the implementation of strategic management of the company's performance where there is a role for dynamic capabilities in achieving sustainability. The main challenge for companies in general is to understand and apply knowledge management in the form of work systems, how to share, use knowledge and store knowledge and dispose of knowledge that is not in line with standard company procedures in the banking industry in Sidoarjo, especially Conventional Rural Banks which are also hit by break-even. Covid pandemic. The research method is quantitative explanatory with a population of 51 Conventional BPRs in Sidoarjo who are members of the Perbarindo banking organization (Association of Bank Indonesia) in the East Java region with 150 employees as a sample using Accidental Sampling questionnaires. The samples that were declared eligible were categorized as Teller, Customer Service, Back Office, Accounting, Marketing, Supervisor, Area Manager. Data were tabulated and analyzed with SEM-PLS Wrap 3.0 software with outer model and inner model analysis. In this study did not care about age and gender as well as education. The results showed that knowledge sharing has a very large effect on employee performance with a significance level of t count greater than t table. Increasing knowledge sharing in the banking industry can be an innovative performance behavior and strategic plan in the context of economic recovery during the Covid 19 Pandemic.